2019
DOI: 10.1002/wrna.1543
|View full text |Cite
|
Sign up to set email alerts
|

Viral modulation of cellular RNA alternative splicing: A new key player in virus–host interactions?

Abstract: Upon viral infection, a tug of war is triggered between host cells and viruses to maintain/gain control of vital cellular functions, the result of which will ultimately dictate the fate of the host cell. Among these essential cellular functions, alternative splicing (AS) is an important RNA maturation step that allows exons, or parts of exons, and introns to be retained in mature transcripts, thereby expanding proteome diversity and function. AS is widespread in higher eukaryotes, as it is estimated that nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 127 publications
0
59
0
Order By: Relevance
“…Alternative splicing is a principal mechanism that contributes to protein diversity in eukaryotes, while regulating physiologically important immune responses during bacterial and viral infections [ 72 ]. Viral infections have been shown to cause global changes in the alternative splicing signatures in infected cells that may arise due to intrinsic factors like polymorphism at the splice sites or due to direct intervention by virulence factors [ 73 , 74 , 75 ]. A previous study on virus-host interactions has demonstrated that the human coronavirus targets various signaling pathways of ER stress, resulting in differential splicing outcomes [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alternative splicing is a principal mechanism that contributes to protein diversity in eukaryotes, while regulating physiologically important immune responses during bacterial and viral infections [ 72 ]. Viral infections have been shown to cause global changes in the alternative splicing signatures in infected cells that may arise due to intrinsic factors like polymorphism at the splice sites or due to direct intervention by virulence factors [ 73 , 74 , 75 ]. A previous study on virus-host interactions has demonstrated that the human coronavirus targets various signaling pathways of ER stress, resulting in differential splicing outcomes [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, alternative RNA splicing was intensively performed by eukaryotes to increase proteome diversity through the formation of numerous mRNA isoforms from a primary transcript and to regulate the expression of proteins in different organs and cell types [22,23]. It was also an important mechanism that had been reported to be used by eukaryotic hosts to regulate their defense systems at the cellular level [20,24,28]. In our transcriptome data, a large number of genes related to the alternative splicing, such as serine-arginine (SR) proteins, ribonucleoprotein, spliceosome, proteasome, were enriched [28,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses had been reported to take use of this strategy to express their own proteins during the infection cycle. Most of them were animal viruses, complex retroviruses and type A influenza virus [24,28]. Although splicing was rarely observed in plant viruses, the splicing of viral mRNA was detected in several plant DNA viruses in two families Geminiviridae and Caulimoviridae [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing is a principal mechanism that contributes to protein diversity in eukaryotes, while regulating physiologically important immune responses during bacterial and viral infections [72]. Viral infections have been shown to cause global changes in the alternative splicing signatures in the infected cells that may arise due to intrinsic factors like polymorphism at the splice sites or due to direct intervention by virulence factors [73][74][75]. A previous study on virus-host interactions has demonstrated that human coronavirus targets various signaling pathways of ER stress resulting in differential splicing outcomes [76].…”
Section: Alternative Splicing Analysis Revealed An Abundance Of Skippmentioning
confidence: 99%